Reduced Anxiety Associated to Adaptive and Mindful Coping Strategies in General Practitioners Compared With Hospital Nurses in Response to COVID-19 Pandemic Primary Care Reorganization - Perilli, Enrico; Perazzini, Matteo; Bontempo, Danilo; Ranieri, Fabrizio; Di Giacomo, Dina; Crosti, Cristina; Marcotullio, Simona; Cobianchi, Stefano (Frontiers in Psychology, 2022)
COVID-19 pandemic imposed psychosocial stress increasing in frontline healthcare workers, who managed by responding with different coping strategies. General practitioners were targeted by an extraordinary increase in the demand for reception, diagnosis and treatment from all patients even if working in solo. In Italy, the emergency changed risk assumption and roles in between primary care, unraveling the emotional distress of general practitioners, who suffered not only for isolation, but also emotional threatens. In this correlational study we wanted to evaluate trait anxiety and stress as perceived by general practitioners working in individual ambulatory practice room, and by hospital ward nurses working in group, during a chronic phase (February - May 2021) of COVID-19 pandemic. Our hypothesis is that a different work social organization in clinic contest as for general practitioners compared with nurses could induce adaptive or non adaptive coping to stress under emergency and mindful attitude could be crucial. A number of 37 general practitioners, and 36 nurses were taken from the sanitary district of ASL1 Avezzano-Sulmona-L’Aquila in Italy. For our analyses we used the Health Professions Stress and Coping Scale to assess the risk of burn-out, and detect the coping strategies. We also used the Cognitive and Affective Mindfulness Scale-Revised, investigating whether clinicians used an eventual mindful attitude to prevent anxiety and responding with adaptive coping strategies. General practitioners reported high levels of anxiety, associated to an increased use of emotional distress. Mindful attitude was protective for anxiety in both general practitioners and nurses. As anxiety increased, it was coped by increasing the demand for social support. This coping strategy correlated with emotional distress and when enhanced, it corresponded to avoidance of the problem. Mindful attitude addressed general practitioners to adaptive coping strategies as the solution of the problem. On the other side, nurses accepted the problem but addressed it to others, by avoiding solving it themselves as beyond their role and organizational responsibility. In conclusion, mindful attitude can prevent dysfunctional reactive behaviors among clinicians at the forefront of emergency and reduce emotional distress for isolation as suffered by general practitioners.